Evaluating the Effectiveness of ISO 9001:2000 Training in Certified Manufacturing Companies in Malaysia - Saleh, Moftah Farag (2004)
With more Malaysian manufacturing companies upgrading from previous standards ISO 9000: 1994 to the ISO 9001: 2000 standards, employee readiness is an important component for successful implementation. The Implementation Team tasked with implementation and maintenance of the standards is trained to facilitate the required transformation. The purpose of this research is to obtain feedback from Implementation Team Members who are responsible for implementation of ISO 9001:2000 standards in their companies. 87 respondents from 27 Malaysian (small and big) Manufacturing companies which had recently implemented the ISO 9001:2000 standards in their work agreed to participate in the this study. The aim of the research was to evaluate training programs conducted to support the implementation of the system. Using Kirkpatrick’s Model this study evaluated the training programs and their influence on the success or failure of quality standards implementation. Analysis of the results showed a high incidence of positive feedback for the reaction, knowledge and attitude levels. The evaluation of the Implementation Team members, skill levels for implementation of clause 6.2.2, considered critical to the success of implementation of the system however was less positive and registered only average ratings. This indicates that training needs for Implementation Team Members need to be given more attention to ensure that they are well prepared to carry out their roles in the implementation process. Additionally, in attempting to investigate the necessity for training on additional skills required to establish and maintain the system the general consensus among them was the requirement for additional training.